Impact of COVID‐19 lockdown on sleep patterns and the related problems among nursing students - Amal Ahmed Elbilgahy; Areej Musaad Alanazi; Badriah Mefrh Alrawili; Rawan Mamdouh Alenezi; Rawan Fahad Alanazi; Amal Khulaif Alanazi; Manal S. Fawzy (Wiley, 2024)
Abstract Aim To evaluate the impact of the COVID‐19 lockdown on sleep patterns and quality among nursing students in our college. Design A cross‐sectional study was carried out. Methods A total of 302 nursing students aged 18-25 years, representing both genders and various academic levels, participated in this study. A pre‐validated, self‐administered questionnaire was used to assess sleep quality during COVID‐19 and it was distributed through various social media platforms for data collection. Results Female students comprised the majority (92.1%) of participants. Of 332 nursing students, 302 completed the questionnaire, yielding a 91% response rate. Statistically significant differences were observed before and during the COVID‐19 lockdown regarding the need to sleep after waking, feeling refreshed upon waking, satisfaction with individual sleep patterns and experiencing restless and troubled sleep (p = 0.001). Additionally, approximately one‐third of nursing students (32.9%) reported poor sleep quality during the COVID‐19 pandemic, with minimal impact on the total sleep hours among the studied cohorts. Public Contribution The COVID‐19 pandemic has statistically significant impacted nursing students' sleep quality and levels. Acknowledging these challenges and planning for providing supporting measurements is essential to ensuring that nursing students can maintain their physical and mental health, which is critical for their ability to provide quality healthcare.